The use of surface appearance in combination with charpy impact energy to determine J-integral values: - Walters, C.L.; Wallin, K. (2013)
This paper gives the theoretical basis for a new method of using Charpy data to estimate fracture toughness in the transition region by using both fracture surface appearance and the traditional Charpy energy. Prior research has shown that the Charpy energy and fracture surface appearance can be used to estimate the upper-shelf J-integral [1]. The current paper extends those ideas by using that same information not to estimate upper-shelf Charpy energy, but to estimate the toughness of fracture mechanics specimens at the same temperature